Augmentation of dural closure following cerebro-spinal surgeries using Evicel- an experience of 105 patients in India - Diyora, Batuk D.; More, Nilesh; Dhali, Gagan (International Surgery Journal, 2021)
Background: For the neurosurgeon, CSF leaks are a frustrating post-operative complication, and for the patient, it can result in unanticipated morbidity and mortality. Immediate intra-operative recognition of incidental durotomy and dural closure may avoid it. Fibrin sealant is a two-component topical hemostat, dura sealant, and tissue adhesive consisting of fibrinogen and thrombin. We conducted this study to evaluate the efficacy of fibrin sealant Evicel in the management of postoperative CSF leaks as an adjunct to dural suture in patients undergoing a variety of neurosurgical procedures. Methods: This was a retrospective, single-center clinical study conducted on 105 patients who underwent elective neurological surgery from August 2015 to May 2016 at Sion Hospital, India. The efficacy endpoint was the prevention of clinically evident and verified postoperative CSF leak. Results: In all patients, the dural defect was effectively repaired intraoperatively, indicated by the absence of CSF leakage. The success rate of using Evicel was 100% in our cohort for the durasealant efficacy. No adverse effects were reported. Conclusions: We conclude that the use of fibrin sealant Evicel was successful to manage CSF leaks and achieve predictable watertight dural closure resulting in a reduction of intraoperative and postoperative fluid collections. It possesses an acceptable safety profile, consistent with previous findings from other similar studies and studies evaluating the role of Evicel in other surgical indications.